Content Marketing Strategy in Building Brand Awareness of Skincare Products From The Perspective of Islamic Business Ethics (Case Study: Skintific) - Adelia Marwa Ujung; Nurbaiti; Tri Inda Fadhila Rahma (Al-Amwal : Journal of Islamic Economic Law, 2025)
Purpose: This study aims to analyze the role of content marketing in building brand awareness of Skintific skincare products from the perspective of Islamic economic law, emphasizing that digital marketing practices must be both effective and compliant with the normative principles of fiqh muamalah. Method: A descriptive qualitative method is employed, collecting data through documentation of digital content and semi-structured interviews with two active Skintific resellers, namely Toko Missglam and Toko Underprice. Analysis is conducted using an Islamic economic law framework to evaluate content marketing practices based on Sharia principles, including honesty (ṣidq), transparency (tablīgh), trustworthiness (amānah), and justice (‘adl), as well as avoidance of deceptive practices (tadlīs) and uncertainty (gharar). Results and Discussion: The findings indicate that content marketing significantly enhances Skintific’s brand awareness through educational content, visual storytelling, and authentic consumer testimonials disseminated via social media. The study introduces a normative perspective, repositioning digital content marketing as a contemporary object of fiqh muamalah, moving beyond mere descriptive marketing analysis toward legal-ethical evaluation. Practices are considered Sharia-compliant as they provide clear and truthful product information and avoid exaggerated or misleading claims, thereby strengthening consumer trust. Implications: This study contributes to the discourse of Islamic economic law by positioning digital content marketing as a contemporary object of fiqh muamalah, offering a normative framework for assessing ethical compliance in modern digital marketing practices. It provides guidance for businesses and scholars on integrating Sharia principles into digital marketing strategies, particularly within the skincare industry.